Peluang dan Tantangan Industri Halal Indonesia Menuju Pusat Industri Halal Dunia - Samsul Samsul; Supriadi Muslimin; Wardah Jafar (Al-Azhar Journal of Islamic Economics, 2022)
The Indonesian government has planned to become the center of the world's halal industry in 2024, but the competition in the halal industry does not only come from Muslim countries also non-Muslim majority countries. Therefore, this study aims to unravel the opportunities and challenges of the Indonesian halal industry towards the center of the world halal industry. This research is a literature study, using a descriptive approach, data and information collected from various kinds of literature and secondary data. The results of this study indicate that there are five aspects of the opportunities for the Indonesian halal industry, aspects of global recognition, finance, halal food, halal tourism, and aspects of halal lifestyle. There are three challenges, each from external sources, competing countries, the unavailability of globally halal certification agreed, and the incompatibility of Muslim countries in lay down halal product standards; and from the internally consists of, the lack of halal awareness among the Indonesian people, the problems of Law Number 33 of 2014 concerning Halal Product Guarantee, and the low awareness of the Indonesian people to compete. In addition to these challenges, there are also obstacles faced of Indonesia, including the halal industry business opportunities that have not been realized by many parties and regulators, the limited supply of raw materials that meet halal criteria, the limited understanding of a number of producers accompanied by inadequate infrastructure, differences in standardization and certification of halal products, and the number of imported products that enter Indonesia.